Contradictions in the situational logic of the university: implications for student success - Kotta, Linda; Case, Jenni; Kathy Luckett, Kathy Luckett (South African Journal of Higher Education, 2018)
Nearly sixteen years into the new democracy, student success at South African universities continues to be differentiated along lines of race. The tendency has been to define the problem in terms of student deficit. This article suggests that this is a limited view of a complex problem. The study investigates the case of a South African university’s engineering department and its historical struggle with the success of black students. It is an exploration of students’ progression through a design course and the associated pedagogical realities. Using a social realist approach, this study shows that the higher education environment is a complex of necessary contradictions which create a situational logic for agents. In the process of navigating the inconsistencies of a system in which academic development and quality assurance work against each other, it seems that black students get caught in the middle, with deleterious consequences for the country’s transformative agenda.